2002
DOI: 10.2135/cropsci2002.1309
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Components of Resistance to Stalk Tunneling by the European Corn Borer in Maize

Abstract: Identification of the genes conferring resistance to European corn borer (ECB) [Ostrinia nubilalis (Hübner)] is an important step in understanding how resistance is expressed and whether different sources of maize (Zea mays L.) germplasm can be combined to enhance protection. The locations of genes for resistance to ECB tunneling have been reported but are inconsistent across studies. The objectives of this study were to map and characterize quantitative trait loci (QTL) for resistance to tunneling in De811 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
6
22
1
Order By: Relevance
“…Concerning the marker coverage, the genetic map of our study was characterized by a higher marker density and a smaller average marker distance (6 cM) compared to previous reports (Schön et al 1993;Cardinal et al 2001;Papst et al 2001;Jampatong et al 2002;Krakowsky et al 2002, Krakowsky et al 2004Cardinal and Lee 2005). Only the two large gaps (about 70 cM) present in the lower arm of chromosome 2 and 8 could have led to a lack of detection of putative QTL present in these regions.…”
Section: Qtl Detectioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Concerning the marker coverage, the genetic map of our study was characterized by a higher marker density and a smaller average marker distance (6 cM) compared to previous reports (Schön et al 1993;Cardinal et al 2001;Papst et al 2001;Jampatong et al 2002;Krakowsky et al 2002, Krakowsky et al 2004Cardinal and Lee 2005). Only the two large gaps (about 70 cM) present in the lower arm of chromosome 2 and 8 could have led to a lack of detection of putative QTL present in these regions.…”
Section: Qtl Detectioncontrasting
confidence: 54%
“…However, in hybrid breeding, use of TC progenies for QTL mapping is more relevant than lines per se, because markers linked to QTL can be employed in MAS only if the identified QTL are expressed in hybrid combinations. Although the resistance to ECB has been shown to be both additive and dominant (Beavis et al 1994, Papst et al 2004, the additive gene action explained most of the genetic variance (Bohn et al 2000;Papst et al 2001;Krakowsky et al 2002). In our mapping population only substituting effects a, equivalent to additive effects in the absence of dominance, could be estimated.…”
Section: Qtl Detectionmentioning
confidence: 85%
See 1 more Smart Citation
“…All QTL found for TC performance were located adjacent to QTL regions detected for stem borer resistance in other temperate and tropical maize populations (Schön et al 1993;Groh et al 1998;Khairallah et al 1998;Bohn et al 2000;Papst et al 2001;Jampatong et al 2002;Krakowsky et al 2002). A compilation of all known QTL positions based on their bin location showed that QTL for stem borer resistance were not randomly distributed across the maize genome but occur in clusters on chromosome 1, 5, and 9.…”
Section: Clustering Of Qtl For Insect Resistancementioning
confidence: 94%
“…In most ECB QTL studies, the majority of QTL associated with resistance showed additive effects and only to a minor extent dominance (Bohn et al 2000;Papst et al 2001;Krakowsky et al 2002). Therefore, tight correlations between per se and TC evaluations were expected.…”
Section: Consistency Of Qtl For Per Se and Tc Performancementioning
confidence: 99%